Phonemic Variations in English Loanwords Borrowed into Afghani Pashto (Journal of Social Sciences Review, 2023)
Due to Pashto-English language contact, a large number of words are borrowed from English into Afghani Pashto. These English loanwords undergo certain types of variation. This study aims at phonemic variations in English loanwords borrowed into Afghani Pashto. A corpus of 90 English loanwords was collected from ten audio-video programs from Afghani TV channels. They were news and discussion panels. The conversation of Afghani Pashto speakers was observed for the collection of the corpus. The data were analyzed according to Levenshtein's (1966) Distance Algorithm Model to investigate the phonemic variations in English loanwords. Based on the research findings, it was revealed that most of the loanwords undergo phonemic variation and some words are just adopted. Most of the words undergo a change of vowel sounds. Some of the words also maintain a change in the consonant sounds. In some cases, the words experience a change in both the vowel and consonant sounds.
Keywords: Language Contact; Loanwords; Phonemic; Variations; Afghani Pashto; English